PERANG SALIB: DARI MOTIVASI RELIGIUS HINGGA AMBISI KEKUASAAN - SEBUAH TELAAH HISTORIS - kinanti, alya dwi; Akbar , Muhammad Hafidh; sitorus, khairi tariq; windari, sri (AL - IBRAH, 2024)
This research discusses the crusades, a series of military campaigns carried out by European Christian powers in the Middle Ages, which had a profound impact not only on the history of Europe and the Middle East but also on global political, religious and cultural dynamics. It was called a crusade because Christian military expeditions when carrying out war used the cross as a unifying symbol to show that the war they were waging was a holy war and aimed to liberate Baitul Magdis (Jerusalem) from the hands of Muslims. The main goal of the crusades was to reclaim the holy land from the Muslim powers who had controlled it for several centuries. This method was used to collect data to reveal the discussion contained in this article. Reference collection in this activity is carried out by studying books and documents that are considered relevant to the object of study. It is hoped that the results of this research will add insight, new knowledge, and understanding of Islamic history and the crusades.